2015
DOI: 10.1049/iet-cds.2014.0248
|View full text |Cite
|
Sign up to set email alerts
|

Uncalibrated operational amplifier‐based sensor interface for capacitive/resistive sensor applications

Abstract: In this paper, a new configuration of operational amplifier-based square-wave oscillator is proposed. The circuit performs an impedance-to-period (Z-T) conversion that, instead of a voltage integration typically performed by other solutions presented in the literature, is based on a voltage differentiation. This solution is suitable as first analogue uncalibrated front-end for capacitive and resistive (e.g. relative humidity and gas) sensors, working also, in the case of capacitive devices, for wide variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Microcontroller Interface (DMI) [21]- [24], and quasi digital schemes namely, resistance to frequency, pulse width or period conversion [27]- [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcontroller Interface (DMI) [21]- [24], and quasi digital schemes namely, resistance to frequency, pulse width or period conversion [27]- [28].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this solution is not suitable for readout system that requires a fast transient response from a high density sensor array with wide resistance range. The quasi digital system converts resistance to frequency, period, or pulse width variation; but another interface circuitry is necessary to covert the quasi digital output to digital, which makes the system complex [27]- [28]. In DMI technique, the microcontroller unit (MCU) excites a passive resistive [21]- [22] or capacitive [23] sensor and then measures the duration of the transient response to reach a predefined threshold using the embedded digital timer.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 gas constituting 76% of the increasing greenhouse gas effect is used in the detection of air quality and in fact has an important role on the global warming (Lin & Fan, 2020; Zhang, Qin, Zhang, Lü, & Hu, 2017). It is observed that the surface acoustic wave, capacitive, infrared, resistive, and solid electrolyte sensors are used to sense the CO 2 gas (Baraton, 1996; Bianchetti, Arrieta, & Walsöe De Reca, 2015; De Marcellis, Ferri, & Mantenuto, 2015; Nieuwenhuizen & Nederlof, 1990; Takeda et al, 2015; Wang et al, 2016). In the resistive sensors, as a result of the interaction of the target gas with the surface, the conductivity (resistance) of sensor material changes and thus an automatically stimulating effect occurs (Hadia, Alqahtani, & Mohamed, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some characteristic properties such as nontoxicity, chemical stability, large area deposition, low‐cost, environmental compatibility, controllability of compositions, uniformity of thickness, photo‐sensitivity/catalytic activity, and tailoring of nanostructures. As well known that for the ZnO nanorod productions there are several deposition methods as regards as the magnetron sputtering (Lin & Fan, 2020), one‐step solid state reaction (Takeda et al, 2015), spray pyrolysis (De Marcellis et al, 2015), electrodeposition (Wang et al, 2016), partly sol–gel (Hadia et al, 2015; Li, Shi, & Hu, 2017), chemical vapor deposition (Jagadale, Patil, Vanalakar, et al, 2018; Patil et al, 2016; Zhang, Qin, et al, 2017), pulsed laser deposition (Nieuwenhuizen & Nederlof, 1990), and hydrothermal (Baraton, 1996; Bianchetti et al, 2015). Among the fabrication processes, the latter method (related to the ZnO nanorods formation on the seed layer [Anajafi, Naseri, & Neri, 2020; Ghosh, Zhang, Zhang, & Shi, 2019; Samarasekara, Yapa, Kumara, & Perera, 2007]) exhibits superior features including the simplicity, cost effectiveness, large area deposition, and flexibility in the compositional modification.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the impedance‐to‐period (Z‐T) conversion becomes suitable in those applications (e.g. sensor interfaces) where a wide variation range and/or a not well‐known baseline occur , while for reduced variations, an impedance‐to‐voltage (Z‐V) conversion is preferred .…”
Section: Introductionmentioning
confidence: 99%